Effect of Double Masking with Silk or Cotton Over-masks on the Source Control Capabilities of a Surgical Mask - Adam F. Parlin; Mikhail Yermakov; Samuel M. Stratton; Susan R. Reutman; Theresa M. Culley; Patrick A. Guerra; Sergey A. Grinshpun (Aerosol and Air Quality Research)
Abstract In spite of the remarkable progress made in the development of safe and effective vaccines against COVID-19, deployment of respiratory protective devices remains vital for mitigating the transmission of SARS-CoV-2 during the ongoing pandemic. In this study, we evaluated double masking, which entails layering a fitted over-mask on top of a surgical mask. A previously validated manikin-based protocol was used to evaluate the performance of a surgical mask with an over-mask made of silk or cotton. We showed that double masking can significantly enhance the mask’s source control capabilities by reducing an aerosol emission from a coughing or sneezing wearer while maintaining a reasonable breathability and comfort level. The data obtained in this study, as well as the results recently reported by other investigators, suggest that an over-mask made of silk fabric has several advantages over one made of cotton. Moreover, silk over-masks have the added benefit of providing a reusable protective outer layer for surgical masks as silk is hydrophobic and increases aerosol particle collection. Not only can double masking reduce viral or bacterial transmission, but it can also promote surgical mask longevity, thereby reducing global waste and pollution associated with the use of disposable surgical masks. Finally, an additional study with five human subjects revealed no significant differences in perceived comfort (measured by proxies such as relative humidity, temperature, and CO2 level inside the mask) between single masking and double masking, as well as between double masking with either a silk or cotton over-mask.